EFEKTIVITAS DAUN RAMANIA ASAL KALIMANTAN SELATAN UNTUK MENURUNKAN KADAR GULA DARAH - Saftia Aryzki; Yugo Susanto (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2019)
Ramania or Gandaria is a swamp plant in the area of South Kalimantan from one of the mango families that is not cultivated by the community, the types are diverse, including fruit size, flavor, and color. Ramania leaves have properties to reduce blood sugar levels. High blood sugar levels are a manifestation of diabetes mellitus. The purpose of this study was to determine the effectiveness of ramania leaf extract as a decrease in blood sugar levels with the oral glucose tolerance test (TTGO) method. This study was a true experimental with a pre-post test design with randomized control group design. The stages of the research method were carried out with a preliminary stage and an antidiabetic activity test stage with an oral glucose tolerance test (TTGO) method with Sprague Dawley strain male rats. The results of the research that have been done can be concluded that the extract of ramania leaf (Bouea macrophylla Griffith) can reduce the blood sugar levels of white mice (Mus muscullus) which are induced by alloxan. The dose used in this study was the lowest dose 0.455 mg / 200 kg body weight, treatment group 2 (P2) with moderate dose (usual use dose) 0.91 mg / 200 g body weight, and treatment group 3 (P3) with high dose 1, 82 mg / 200 g BW. Of the three groups approaching positive control, P3 with blood sugar levels after 14 days of treatment was 77.08 mg / dL and 77.79 mg / dL, respectively.